Observation of a non-Hermitian phase transition in an optical quantum gas - Öztürk, Fahri Emre; Lappe, Tim; Hellmann, Göran; Schmitt, Julian; Klaers, Jan; Vewinger, Frank; Kroha, Johann; Weitz, Martin (Science (American Association for the Advancement of Science), 2021)
Our textbook understanding of quantum systems tends to come from modeling these systems isolated from the environment. However, an emerging focus is understanding how many-body quantum systems behave when interacting with their surroundings and how they subsequently become dissipative, or non-Hermitian, systems. Öztürk et al. formed a quantum condensate of light by trapping photons in an optical cavity, a system that is naturally dissipative. By altering the trapping conditions, they demonstrated that the system provides a powerful platform with which to explore the complex dynamics and phase transitions occurring in dissipative quantum systems. Science , this issue p. 88 A photon condensate is used to model the behavior of dissipative quantum systems. Quantum gases of light, such as photon or polariton condensates in optical microcavities, are collective quantum systems enabling a tailoring of dissipation from, for example, cavity loss. This characteristic makes them a tool to study dissipative phases, an emerging subject in quantum many-body physics. We experimentally demonstrate a non-Hermitian phase transition of a photon Bose-Einstein condensate to a dissipative phase characterized by a biexponential decay of the condensate’s second-order coherence. The phase transition occurs because of the emergence of an exceptional point in the quantum gas. Although Bose-Einstein condensation is usually connected to lasing by a smooth crossover, the observed phase transition separates the biexponential phase from both lasing and an intermediate, oscillatory condensate regime. Our approach can be used to study a wide class of dissipative quantum phases in topological or lattice systems.